CIRCUMFERENTIAL INHOMOGENITY ANALYSIS IN G.A. SIWABESSY REACTOR’S PRIMARY COOLING PIPE - Himawan, Roziq; Susmikanti, Mike (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2016)
In the in-service inspection conducted to G.A. Siwabessy reactor’s primary cooling system pipe, it was found the presence of inhomogenity inside of welding part. To verify whether the inhomogenity could be tolerated or not, comparative data from welding pre-service inspection is needed. Unfortunately, this weld wasn’t covered in pre-service inspection. Therefore, this inhomogenity needs to be analyzed. The purpose of this study is to evaluate the stress intensity factor of the inhomogenity, whether it is within a limit value or not and to predict the crack growth. Analysis were performed based on fracture mechanics theory using parameter of stress intensity factor. Two models were used for calculation approach that are plane crack model and semi-elliptic crack model. Hence, in order to predict the length of inhomogenity in the future, crack growth calculations were performed. The results showed that stress intensity values from both two models are remain below fracture toughness value of pipe’s material. Besides that, stress intensity factor from plane crack model is higher than those from semi-elliptic crack model. Under consideration that inhomogenity has an arc shape in actual, thus, stress intensity factor from this inhomogenity still low enough compare to the fracture toughness. Crack growth calculation’s results showed that after 300th cycle of loading, the length of inhomogenity reaches approximately 2 mm. Based on operation data of G.A. Siwabessy reactor, 300 cycle number is corresponds to 30 years operation. Based on these results it could be concluded that the presence of inhomogenity in the welding part does not affect the structure’s integrity of piping system.